Short‐term effect on the ocular circulation induced by unilateral intravitreal injection of aflibercept in age‐related maculopathy. Issue 6 (27th March 2019) - Mursch‐Edlmayr, Anna Sophie; Luft, Nikolaus; Podkowinski, Dominika; Ring, Michael; Schmetterer, Leopold; Bolz, Matthias
Abstract: Purpose: Intravitreal injection of anti‐vascular endothelial growth factor (anti‐VEGF) is the standard treatment for neovascular age‐related macular degeneration (AMD). As VEGF is a physiological key player for regulating retinal vascular tone, questions have been raised whether the application of anti‐VEGF could induce alterations in ocular perfusion. Methods: The study included 20 eyes from 20 Caucasian patients with unilateral neovascular AMD and 20 fellow eyes. All eyes were treated with standard intravitreal injection of aflibercept (IVA). Measurements of blood flow at the optic nerve head (ONH) and the choroid were performed with laser speckle flowgraphy (LSFG). The intraocular pressure (IOP), systolic and diastolic blood pressure, heart rate, mean arterial pressure (MAP) and ocular perfusion pressure (OPP) were analysed. Measurements were performed at baseline and repeated immediately after the injection and 30 and 45 min later. Results: Mean time between injection of aflibercept and first follow‐up was 8:56 ± 4:25 min. The injection led to significant rise in IOP. In the injected eyes, mean blur rate (MBR, i.e. a relative measure of perfusion and the main outcome parameter of LSFG) within the major vessels of the ONH as well as at the entire ONH region decreased significantly (p < 0.001). No change in MBR was observed in the fellow eye. Choroidal blood flow was maintained stable in both eyes. Conclusion: Intravitreal injection of aflibercept (IVA) led to a short‐term reduction in perfusion only in the treated eye. This was independent from IOP, indicating a direct pharmacological effect. No changes in choroidal perfusion were observed during the first 45 min after the injection.